PENGARUH PENDAPATAN ASLI DESA, DANA DESA, DAN ALOKASI DANA PERIMBANGAN DESA TERHADAP BELANJA DESA (Studi Kasus pada Desa di Kabupaten Bandung Tahun 2017) - Shofa Irawan, Mutiara Alya; Rahayu, Sri; Aminah, Wiwin (Aksara Public, 2018)
In order to comply the regional autonomy, the central government expects the village government to play a role in contributing to national scale development. In this process of creating the potential development and establishment, the village government needs to increase their village’s expenditure budgets. This study aims to find out the effect of a Village’s Original Income (VOI), Village’s Funds (VF) and Village’s Balance Funds Allocation (VBFA) both simultaneously and partially on Village’s Expenditures in Bandung Regency in 2017. The data used in this study was taken from Village’s Financial Reports Bandung Regency. The analytical method of this study are descriptive statistical analysis, multiple linear regression analysis, classic assumption test and hypothesis testing using IBM SPSS 25 software.Based on the results of the test, it is shown that VOI, VF, and VBFA simultaneously influence Village’s Expenditures with a determination coefficient of 93,4%. As well as the results of the partial test, it is shown that both VOI, VF, and VBFA have a significant positive effect on Village’s Expenditure.